A study on correlation of liver function test and serum bile acid with feto-maternal outcome in patients with intrahepatic cholestasis of pregnancy - Gupta, Sonam; Srivastava, Juhi; Chetia, Modhusmita; Uniyal, P. C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Intrahepatic cholestasis of pregnancy (ICP) is the foremost liver disorder, presenting substantial risks and complications to maternal and fetal health. Characterized by pruritus and elevated bile acids and serum transaminases. Methods: The study focuses on profiling 70 patients of ICP understanding the correlations between liver function tests with serum bile acid and evaluating the impact of ursodeoxycholic acid (UDCA) treatment and also focus on various maternal and fetal outcome. Results: The study identified a predominance of primigravida (68.6%) of 26-30 years of age (47.1%), often needing hormonal support (34.3%), with a high incidence of abnormal CTG findings (28.6%) and fetal distress (17.1%) with maximum patient with moderate serum bile acid levels. IHCP diagnosis was commonly noted between 32-36.6 weeks GA (57.1%). The treatment with UDCA 300-TDS (in 72.9% patient) was providing relief to about 75% of participants within a week. Most deliveries occurred between 37-39 weeks (70%) GA, predominantly via LSCS (54.3%), NVD (35.7%) and assisted vaginal delivery (10%). PPH was seen in 4.3% patients. Fetal outcomes revealed 40% incidence of meconium-stained liquor and about 12% NICU admissions with no fetal mortality. Most participants (78.6%) had serum bile acid levels in the 10-40 µmol/L range. Conclusions: Significant correlations were noted between SGOT and SGPT and with ALP and bile acid. In contrast, bilirubin showed no significant correlations. Higher UDCA dosages showed a dose-response relationship, implying their effectiveness in managing ICP.